Does external debt promote economic growth in Côte d’Ivoire? - TOAMA, Boke Aime Arnauld (KDI School, 2019)
The paper calls attention to the increasing external debt in Côte d’Ivoire. The primary goal of this paper was to cast light on the nature of the correlation between external debt and economic growth. I also attempted to identify the optimal level of debt stock that the country should hold for growth. The Autoregressive Distributive Lag (ARDL) bound test was performed to test for the presence of a cointegrating relationship between external debt and economic growth. I also employed the Hansen (2000) threshold test so as to confirm the presence of a threshold effect in external debt. The results suggest that external debt and economic growth are cointegrated. External debt significantly promoted growth in the longrun. The threshold test confirmed the presence of a threshold effect of external debt on economic growth, meaning that the Ivorian external debt and growth display a non-linear relationship. However, the number of observations did not allow the estimation of the threshold.
Thesis(Master) --KDI School:Master of Public Policy,2019